Hubungan Pengetahuan dan Sikap Ibu Nifas dengan Pemberian ASI Ekslusif di Ruang Kasuari RSU Anutapura Palu - Rosiyana, Ni Made; Ayu, Dewi Sry; Pratiwi, Vira (Poltekkes Kemenkes Palu, 2019)
Breastmilk has several advantages when compared to formula milk. Breastmilk is cheap, healthy, and easy to give. The provision of exclusive breastfeeding in the city of Palu increased relatively in 2015 (68%) to 2016 (64%). While respecting exclusive breastfeeding at Anutapura General Hospital in Palu in 2016 (74%) or 1,462 of the total births of 1954 and not yet reaching the national target of 80%. This study is an analytical study that uses Cross-sectional with a sample of 48 respondents. Statistical test results from the knowledge of postpartum mothers with the help of Exclusive ASI obtained p-value = 1,000 in the exact test, with a confidence level of Î± = 0.05, so the value of p> Î± then H1 is accepted and H0 is supported, allowing statistics there is no relationship between maternal knowledge childbirth with exclusive breastfeeding. While the results of statistical tests of postpartum mothers' attitudes with exfoliated breastfeeding obtained a p-value = 0.009 in Chi-square test, with a confidence level of Î± = 0.05, so the p value <Î± then H1 was accepted and H0, according to statistics there was a relationship between attitudes postpartum mothers with exclusive breastfeeding. So conclusions can be drawn between no relationship between knowledge of postpartum mothers and exclusive breastfeeding and there is a relationship between postpartum maternal attitudes and the provision of exclusive breastfeeding at Anutapura Hospital Palu.